Addition of proline-rich whey peptides during dehydration increases solubility of rehydrated milk protein concentrates. (October 2018) - Torres-Hernandez, Marcela; Howell, Kate; Bennett, Louise E.
Abstract: Protein solubility of milk protein concentrate (80% protein; MPC80) is compromised by condition-dependent processing and storage due to both physical and chemical self-association of caseins. Solubility of MPC80 was studied following storage at 4 °C to selectively focus on efficacy of adding the whey-proline rich peptide hydrolysate, 'DISSPEP', in regulating physical protein aggregation processes. A range of concentrations of total solids [5% (control), 50%, 90%, w/w], DISSPEP [0% (control), 5%, 10%, 25% of solids substituted], storage and rehydration pH (6.0, 6.5, 7.5) and storage time [0 (control), 7, 14 days], were examined. Relative to controls, the addition of DISSPEP generally improved MPC80 protein solubility by factors of 50–600%, dependent on storage time and pH. DISSPEP was particularly effective for rehydrating MPC80 following concentration and drying to 50%–90% solids, respectively. The results suggest potential industrial usefulness of DISSPEP for improving solubility of MPCs, particularly at low temperatures.